2013
DOI: 10.1002/jsfa.6206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic, conventional and mixed cultivation practices on soil microbial community structure and nematode abundance in a cultivated onion crop

Abstract: . (2013), Effect of organic, conventional and mixed cultivation practices on soil microbial community structure and nematode abundance in a cultivated onion crop, J. Sci. Food Agric., 93: 3700-3709. doi: 10.1002/jsfa.6206 which has been published in final form at http://onlinelibrary.wiley.com/doi/10.1002/jsfa.6206/full.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
4
24
1
2
Order By: Relevance
“…Our results are corroborated with those of Mishra et al (1987) who found 832 actinomycetes, 70 fungus and 40 bacterial isolates from various soil types and reported the predominantly active 27 strains with insecticidal and nematicidal traits as actinomycetes. Our results are further supported by Polyanskaya et al (1996), who isolated antibiotic heliomycin producing actinomycete S. olivocinereus from earthworm E. foetida and Reilly et al (2013), who observed higher microbial communities and activities in organic fields compared with farming systems utilising conventional agriculture.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are corroborated with those of Mishra et al (1987) who found 832 actinomycetes, 70 fungus and 40 bacterial isolates from various soil types and reported the predominantly active 27 strains with insecticidal and nematicidal traits as actinomycetes. Our results are further supported by Polyanskaya et al (1996), who isolated antibiotic heliomycin producing actinomycete S. olivocinereus from earthworm E. foetida and Reilly et al (2013), who observed higher microbial communities and activities in organic fields compared with farming systems utilising conventional agriculture.…”
Section: Discussionsupporting
confidence: 93%
“…However, when compare to unfertilized control soil, both OM and IC having significantly higher 16S rRNA gene abundance clearly explained that the fertility source (either organic or inorganic) is the dominant factor driving the bacterial community structure (Esperschutz et al, 2007;Widmer et al, 2006) and 16S RNA gene density (Orr et al, 2011). Increase of SOC associated with nutrient management had positive correlation with soil bacterial diversity (Jangid et al, 2008;Zhong and Cai, 2007) and abundance (Reilly et al, 2013).…”
Section: Long Term Organic and Inorganic Fertility Managements Favor mentioning
confidence: 90%
“…Although positive effects of organic management have been widely reported (Liu et al, 2007; Ge et al, 2008; Jonason et al, 2011; Hartmann et al, 2015), the effects of farming systems on diversity of microbial communities are complex and commonly controversial (Kleijn et al, 2001). Ge et al (2008) found an increase in diversity after manure amendment, and other studies reported no differences or decrease in bacterial diversity and richness when organic systems were compared to conventional management (Liu et al, 2007; Reilly et al, 2013). Bengtsson et al (2005) argue that in most cases, organic farming can be expected to benefit the biodiversity, but the effects will differ between organism groups and landscapes.…”
Section: Introductionmentioning
confidence: 85%
“…Effects of farming systems on microbial communities are complex and time-dependent (Jonason et al, 2011). In general, it has been reported that management practices in organic farming systems change the microbial composition toward a more fast growing community (copiotrophic community) due to nutrients (Chaudhry et al, 2012), promote habitat diversification, increase the diversity and sustainability, and benefit microbial taxa involved in plant health when compared to conventional farming systems (Esperschutz et al, 2007; Sugiyama et al, 2010; Reilly et al, 2013; Gonthier et al, 2014). However, up to date, there are no studies about microbial community heterogeneity, which we refer as microbial community variability, in different farming systems.…”
Section: Introductionmentioning
confidence: 99%